Tax Sanctions as a Moderator of Behavioral and Technological Factors in Compliance: Sanksi Pajak sebagai Moderator Faktor Perilaku dan Teknologi dalam Kepatuhan - Ermadiani Ermadiani; Rina Tjandrakirana DP; Apriyansyah Apriyansyah; Alditya Aris Rinandy; Bella Adelia (Academia Open, 2025)
General Background: Tax compliance is a fundamental component of Indonesia’s revenue system, particularly under the self-assessment mechanism that relies on taxpayer honesty and awareness. Specific Background: Despite various incentives and reduced tax rates, the Micro, Small, and Medium Enterprises (MSME) sector continues to exhibit low compliance levels. Prior research has overlooked the integrated role of behavioral, technological, and enforcement factors in shaping tax compliance. Knowledge Gap: Limited studies have examined how money ethics, artificial intelligence (AI), tax rates, and tax audits influence MSME tax compliance when moderated by tax sanctions. Aims: This study aims to analyze the effects of these four variables on MSME taxpayer compliance in South Sumatra, with tax sanctions as a moderating variable. Results: Using moderation regression analysis on data from 110 MSME respondents, findings reveal that money ethics, AI, and tax audits significantly affect compliance, while tax rates do not; tax sanctions significantly strengthen all relationships. Novelty: This research integrates moral, technological, and regulatory perspectives through the Theory of Planned Behavior, presenting a new framework for compliance analysis in the digital taxation era. Implications: The study provides practical guidance for policymakers to enhance MSME tax compliance via balanced moral education, AI-based systems, and fair but firm enforcement measures. Highlights:  Combines moral, technological, and regulatory factors in tax compliance analysis. Shows tax sanctions strengthen behavioral and AI impacts on compliance. Provides policy insights for enhancing MSME tax compliance in Indonesia. Keywords: Money Ethics, Artificial Intelligence, Tax Sanctions, Tax Compliance, MSMEs